2014
DOI: 10.3846/16486897.2013.872117
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ph in Heavy Metal Contamination of Urban Soil

Abstract: The aim of this study to assess interdependence between urban soil pH and its accumulation of heavy metals. The article meant to be a contribution to a better knowledge of peculiarities and diagnostics of urban soil and its anthropogenic transformation. The hypothesis assumes that relationship between urban soil pH and its accumulation of heavy metals may be determined by the origin and age of parent material as well as the nature and degree of the anthropogenic impact. The spatial variability of topsoil pH le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
(19 reference statements)
0
9
0
3
Order By: Relevance
“…Furthermore, we found that the toxic effect of heavy metals was relatively higher in FQ soil than in NB soil. Previous studies indicated that the higher pH value decreased the availability of heavy metal concentrations in soils (Kazlauskaitė-Jadzevičė, Volungevičius, Gregorauskienė, & Marcinkonis, 2014). However, the mobility and availability of antibiotics and heavy metals also depends on organic carbon content, clay minerals, inorganic anions, and cations, etc.…”
Section: Otc and Cu/zn On Nitrification Processmentioning
confidence: 99%
“…Furthermore, we found that the toxic effect of heavy metals was relatively higher in FQ soil than in NB soil. Previous studies indicated that the higher pH value decreased the availability of heavy metal concentrations in soils (Kazlauskaitė-Jadzevičė, Volungevičius, Gregorauskienė, & Marcinkonis, 2014). However, the mobility and availability of antibiotics and heavy metals also depends on organic carbon content, clay minerals, inorganic anions, and cations, etc.…”
Section: Otc and Cu/zn On Nitrification Processmentioning
confidence: 99%
“…в бік підвищення лужності на всіх ділянках, що, ймовірно, пов'язано з надходженням в ґрунт лужних агентів при таненні снігу, а також розчиненням материнських порід (реакція середовища лесових порід рH вод. змінюється в межах 6,[7][8]9).…”
Section: рисунок 3 -ранжування ґрунтів за рн водunclassified
“…Більшість рослин потребує для свого розвитку нейтральної або слабко лужної реакції, тому визначення реакції середовища, джерела її утворення є основою для відтворення родючості ґрунту. У міських умовах ґрунти зазвичай лужні [2][3][4][5][6][7], хоча зустрічаються і кислі [8][9][10]. В цілому процес незначного залуження ґрунту сприятливо позначається на його властивості і родючості, зокрема, знижується ступінь рухливості металів, що позитивно впливає на ріст і розвиток рослин, сприяє активізації мікробного співтовариства.…”
unclassified
“…У міських умовах ґрунти зазвичай лужні [1,[9][10][11][12], хоча трапляються і кислі [13][14][15]. В цілому процес незначного залуження ґрунту сприятливо позначається на його властивості та родючості, зокрема, знижується ступінь рухливості металів, що позитивно впливає на ріст і розвиток рослин, сприяє активізації мікробного співтовариства.…”
Section: рисунок 4 -розподіл ґрунтів за кислотністюunclassified